A COP1-HY5-ABI5 module regulates ABA-mediated post-germination developmental arrest - Singh, Deeksha; Yadukrishnan, Premachandran; Rahul, Puthan Valappil; Datta, Sourav (Frontiers in Plant Physiology, 2025)
Abscisic Acid (ABA) is a key phytohormone that regulates plant development under stress. ABA induces dormancy in seeds during maturation, whereas its levels and activity gradually decrease as germination and seedling growth progress. Under abiotic stress conditions, elevated levels of ABA inhibit seed germination and/or impose post-germination growth arrest. The transcription factor ABSCISIC ACID INSENSITIVE 5 (ABI5) regulates the interplay between ABA and light signaling to modulate this process. The light-regulated transcription factor ELONGATED HYPOCOTYL 5 (HY5) modulates ABA-mediated inhibition of post-germination development. However, the interrelation between HY5 and ABI5 in regulating post-germination development remains poorly understood. Here, using molecular, genetic, and biochemical approaches, we show that ABI5 and HY5 proteins reciprocally influence each other’s accumulation during early plant development. We further find that ABA induces nuclear accumulation of COP1, which correlates with reduced HY5 levels and enhanced ABI5 accumulation under stress conditions. Together, our results support a model in which a double-negative feedback loop between HY5 and ABI5 contributes to ABA-mediated post-germination growth arrest.